Socio-economic status and health care utilization in rural Zimbabwe: findings from Project Accept (HPTN 043) - Sebastian Kevany; Oliver Murima; Basant Singh; Daniel Hlubinka; Michal Kulich; Stephen F. Morin; Michael Sweat (AOSIS, 2012)
Zimbabwe's HIV epidemic is amongst the worst in the world, and disproportionately effects poorer rural areas. Access to almost all health services in Zimbabwe includes some form of cost to the client. In recent years, the socio-economic and employment status of many Zimbabweans has suffered a serious decline, creating additional barriers to HIV treatment and care. We aimed to assess the impact of i) socio-economic status (SES) and ii) employment status on the utilization of health services in rural Zimbabwe. Data were collected from a random probability sample household survey conducted in the Mutoko district of north-western Zimbabwe in 2005. We selected variables that described the economic status of the respondent, including: being paid to work, employment status, and SES by assets. Respondents were also asked about where they most often utilized healthcare when they or their family was sick or hurt. Of 2,874 respondents, all forms of healthcare tended to be utilized by those of high or medium-high SES (65%), including private (65%), church-based (61%), traditional (67%), and other providers (66%) (P=0.009). Most respondents of low SES utilized government providers (74%) (P=0.009). Seventy-one percent of respondents utilizing health services were employed. Government (71%), private (72%), church (71%), community-based (78%) and other (64%) health services tended to be utilized by employed respondents (P=0.000). Only traditional health services were equally utilized by unemployed respondents (50%) (P=0.000). A wide range of health providers are utilized in rural Zimbabwe. Utilization is strongly associated with SES and employment status, particularly for services with user fees, which may act as a barrier to HIV treatment and care access. Efforts to improve access in low-SES, high HIVprevalence settings may benefit from the subsidization of the health care payment system, efforts to improve SES levels, political reform, and the involvement of traditional providers.